The Bank Account is not Enough: Examining Strategies for Financial Inclusion in India - Morawczynski, Olga; Hutchful, David; Rangaswamy, Nimmi; Cutrell, Ed (Proc. of the 4th IEEE/ACM Conference on Information and Communication Technologies and International Development (ICTD) 2010, London, UK, IEEE, 2010)
The Indian government has undertaken an ambitious strategy for financial inclusion (FI) as part of its development agenda. With the aid of technology-enabled branchless banking initiatives, this drive has been successful in regards to extending access—nearly 60% of the Indian population is banked. However, empirical evidence suggests that the majority of bank accounts are not being utilized, especially not by the poor who are the target of FI. This paper examines the reasons for such underutilization and also recommends ways to improve the FI drive. The paper contributes to the strand of ICTD literature that focuses on FI in two ways. First, it makes clear that the measures of FI success should not be focused on access alone. The real impact comes from appropriate usage of these accounts. Second, it argues that financial education (FE) should be integrated into the FI drive. This would help the poor to more effectively exploit their links to formal financial services and decrease their reliance on costly informal alternatives.